PERANCANGAN SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG DAGANG BAGI USAHA MIKRO KECIL MENENGAH (UMKM) PADA TOKO KOSMETIK MF SHOPPU (1) - 'Atikah, Azian Nikhlatul; Bhilawa, Loggar; Aji, Susilo (JURASIMA, 2024)
This research aims to design a web-based inventory accounting information system at MF Shoppu cosmetic store which has been recording inventory manually. This manual recording makes it difficult for shop owners to monitor stock items in real-time, causing delays in order fulfillment and potential losses due to retail purchases. The research method used is the Waterfall approach, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The results of this study indicate that the inventory accounting information system developed can assist store owners in managing inventory data automatically and in real-time. Thus, this system is able to improve the efficiency of inventory management and help store owners in making faster and more accurate decisions.